Strategic Entrepreneurship Alliances and Sustainable Growth of Small Businesses in Nigeria: The Nexus (Global Journal of Management and Business Research, 2022)
Due to high operational costs operational risks and the inability of SMEs to access resources business activities in Nigeria have remained largely unsustainable over time Small businesses must be able to overcome these obstacles if they want to remain viable globally This paper is aimed at investigating the relationship between strategic entrepreneurship alliance and sustainable growth of small businesses in Nigeria With a population of three thousand and fifteen 3015 registered small businesses in Abuja Metropolis and using Bartlett Kotrlik and Higgins 2001 model of minimum sample size determination a sample size of 520 respondents was obtained and a questionnaire was the only data collection instrument employed in the study It was revealed that both vertical and horizontal integrations are strongly related to the growth and sustainability of small businesses in Abuja Metropolis The study concluded that a strategic entrepreneurship alliance is pivotal for small business growth sustainability and recommended that small businesses desirous of growth and expansion through improved competitive positioning and gain entry into new markets supplement critical skills and share the risk and cost of major developmental projects should strategically ally and collaborate with other firms to ensure a continuous flow of inputs for uninterrupted operations resulting to effective efficient and reliable product distribution chain that guarantees firm s growth and sustainability
Keywords: strategic entrepreneurship; strategic alliances; vertical integration; horizontal integration; and sustainable business growth